Agenda Pengembangan Perbankan Syariah untuk Mendukung Sistem Ekonomi yang Sehat di Indonesia: Evaluasi, Prospek dan Arah Kebijakan - Mulya Siregar (Jurnal Iqtisad, 2002)
Even though shariah banking has been legally exist in Indonesia since 1992, its development still face some constraints Actually, the development of shariah banking is an soundness of national  integral part of developing banking system and strengthening the economic fundamental. So, a good cooperation among stakeholder of shariah banking is strongly needed a market driven, fair treatment, gradual and sustainable, and Islamic values oriented policy are important paradigm for developing a sound shariah banking system. Besides evaluating economic performance of shariah bank and predicting its prospect in the future, this paper also discuss the paradigm, direction and strategic policy for developing shariah banking in Indonesia.